The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/fst.17420
|View full text |Cite
|
Sign up to set email alerts
|

Promoting effects of 6-Gingerol on probiotic adhesion to colonic epithelial cells

Abstract: Materials and methods MaterialsCaco-2 cell line was purchased from the Key Laboratory of Dairy of Northeast Agricultural University. NCM460 cell line was purchased from Guangzhou Biotechnology Co., Ltd. Two strains of probiotics Lactophilus acidophilus (AS1.2686

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Epidemiological data in 2016 showed that there were 53,070 new cases of pancreatic cancer in the United States, ranking the fourth place in the mortality of malignant tumors. In addition, the incidence rate of pancreatic cancer is increasing year by year (Sancho-Albero et al, 2020;Jiang et al, 2021). Pancreatic cancer is highly of malignant, with extremely poor prognosis (5-year survival rate less than 5%) (Goral, 2015;Heinrich & Lang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data in 2016 showed that there were 53,070 new cases of pancreatic cancer in the United States, ranking the fourth place in the mortality of malignant tumors. In addition, the incidence rate of pancreatic cancer is increasing year by year (Sancho-Albero et al, 2020;Jiang et al, 2021). Pancreatic cancer is highly of malignant, with extremely poor prognosis (5-year survival rate less than 5%) (Goral, 2015;Heinrich & Lang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] We posit that such outcomes are rooted in prebiotics’ ability to: (1) hinder bacterial metabolism by suppressing nucleotide synthesis, chelating essential ions, interacting with cell membrane components, and facilitating electron transfer, [ 28,70 ] (2) serve as a source of energy for intestinal microbiota, [ 30 ] and (3) foster adhesion of probiotics to cells. [ 71,72 ]…”
Section: Mechanisms Underlying the Efficacy Of Pro‐ And/or Prebiotics...mentioning
confidence: 99%
“…[29] We posit that such outcomes are rooted in prebiotics' ability to: (1) hinder bacterial metabolism by suppressing nucleotide synthesis, chelating essential ions, interacting with cell membrane components, and facilitating electron transfer, [28,70] (2) serve as a source of energy for intestinal microbiota, [30] and (3) foster adhesion of probiotics to cells. [71,72] Collectively, the aforementioned research bears witness to use of pro-and/or prebiotics for promoting the proliferation and diversity of beneficial bacteria while impeding populations of harmful microbes within the gut. The development of regimens that include pro-and/or prebiotics may be a novel paradigm for the prevention and treatment of CRC, although further investigations are required to determine which types, dosages, and usage frequencies are most appropriate.…”
Section: Balance Of the Intestinal Microflora Compositionmentioning
confidence: 99%
“…Probiotics are supposed to be beneficial or to prevent the production of biogenic amines and act as bactericidal components. Thus, the adhesion of probiotics would be promoted the strengthen of the beneficial effects of probiotics (Buran et al, 2022;Jiang et al, 2021;Moghadam et al, 2022). Probiotics are harmless microorganisms that, when delivered to humans in sufficient concentrations and for long enough periods of time, have certain beneficial effects on the host.…”
Section: Introductionmentioning
confidence: 99%